Manajemen Krisis Hubungan Masyarakat Bawaslu Kabupaten Kudus dalam Merespon Kampanye Money Politic pada Pilkada Kudus Tahun 2024 - anasytasya, Lea; Addiansyah, M Nur Rofiq (Jurnal Administrasi dan Kebijakan Publik, 2025)
The purpose of writing this article is to explain and analyze the crisis management of Bawaslu Kudus's public relations in responding to the money politics campaign in the Kudus district election campaign in 2024. This reseach employs qualitative methods to provide detailed explanations of events and experiences with detailed and complete data collection through interviews with the public relations of Bawaslu Kudus. In this study the authors used a qualitativ methods. Then in order to obtain appropriate data, the author in collecting data through observation, interviews and documentation. In this case, the public relations of Bawaslu Kudus as a liaison with the community, carried out crisis management in addreessing the money politics campaign carried out in the 2024 Kudus Pilkada. The public relations of Bawaslu Kudus Regency identified this crisis through the report of participatory community supervision and the team formed by Bawaslu Kudus Regency such as ad hoc, Panwascam, and PKD. In its crisis management, the public relations of Bawaslu of Kudus Regency also responded to this crisis swiftly, inviting collaboration with relevant stakeholders, conducting socialization of community participatory supervision, responsively instructing Panwascam to participate in citizen forums to voice anti-money politics, and actively campaigning against money politics through outhreach activites, including street demonstrations.